Answers

2015-07-02T11:07:50+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
6mn-10mn-12m=0
-4mn=12m (transpose -12m to the right side it became +12m)
-4mn=12m (divide both side by 4m to cancel m and to reduce it to lowest form) it b'comes
-n=3
so n=3,
substitute n=3 to the original eq'n
u wil get the value of m..
6m(3)-10m(3)-12m=0
m=0
0